Correction: Preparation and characterization of primary magnesium mixtures for the ab initio calibration of absolute magnesium isotope ratio measurements. Issue 11 (4th October 2019) - Brandt, Björn; Vogl, Jochen; Noordmann, Janine; Kaltenbach, Angela; Rienitz, Olaf
Abstract : Correction for 'Preparation and characterization of primary magnesium mixtures for the ab initio calibration of absolute magnesium isotope ratio measurements' by Björn Brandt et al., J. Anal. At. Spectrom., 2016, 31, 179–196.